ADVANTAGEOUS WHITE HEAD CABBAGE HYBRIDS SUITABLE FOR LONG-STORAGE IN THE SOUTH OF AMUR OBLAST - V. F. Kirsanova (Овощи России)
White head cabbage (Brassicа oleracea L.) is the most widespread crop. Climatic condition in Amur oblast is very favorable to cultivate cabbage crop that has been traditionally used. However, there are released cultivars ‘Podarok’, ‘Nadezhda’, ‘Belorusskaya 455’, ‘Moscovskaya pozdnaya 15’ that do not meet all requirements for economically valuable traits. Results of study of cabbage collection including local and foreign hybrids have been carried out in soil and climatic condition of open field in Amur oblast. Advantageous hybrids with set of economically valuable traits have been selected out to be used and recommended for cultivation in crop farming of Amur oblast.